The Agia Sofia’s Axis. A Corridor of Change and Resilience for Thessaloniki - Maria Ananiadou-Tzimopoulou; Sofia Tzimopoulou; Panagiota Mouratidou (Fábos Conference on Landscape and Greenway Planning, 2016)
The paper dwells on greenways as natural and cultural corridors, and their value for the contemporary city change and resilience. Just after a short theoretical approach on urban landscape architecture related to the sustainability and urban resilience, we intend to present our project that won the second prize in the Panhellenic competition, organized by the Greek Ministry of Environment and Energy, for the redesign of Agia Sofia’ s axis, one of the main historical traces of Thessaloniki’ s urban landscape. This example supports our design approach, socio-ecological and perceptual, for landscape architectural projects, in both planning and design.
Keywords: greenways; Thessaloniki; greece; agia sofia; resilience